Community Preparedness for the Tsunami Ready Community Program: Evidence from Sidoharjo Village, Kebumen Regency, Indonesia - Rubeda, Tangkas Wigawe Tri; Nurdin, Elan Artono; Astutik, Sri; Yushardi (Department of Geography Education, University of Jember, 2026)
Indonesia's location along the Pacific Ring of Fire at the intersection of the Indo Australian, Eurasian, and Pacific plates exposes its coastal areas to severe geological hazards. Despite high disaster risk indices, community preparedness in tsunami prone zones remains suboptimal. This study evaluates the implementation of the Tsunami Ready Community program, based on 12 international indicators, to foster a tsunami prepared culture in Sidoharjo Village, a coastal area vulnerable to megathrust events. Using an exploratory sequential mixed methods design, quantitative data were gathered from a purposively selected sample calculated via the Slovin formula with a 10 percent margin of error, complemented by qualitative observations, interviews, document analyses, and literature reviews. The findings reveal that community preparedness reached a ready status, scoring 74.09 percent. The program significantly enhanced local disaster readiness, particularly in disaster knowledge, emergency preparation, early warning response, and resource mobilization. These results demonstrate that institutionalizing international preparedness standards can effectively bridge the gap between disaster vulnerability and community resilience in high risk megathrust zones.